Language Choice in the Bilingual Bugis Community in Peninsular Malaysia - Syed Jaafar, Sharifah Raihan; Anuardin, Aliah Afiqah (2022)
The Bugis community in Malaysia has to adapt to a more dominant local language, namely Malay language, for survival. The objective of this study is, (1) to identify the languages used by the community, (2) to analyse the language choice used in the primary domains that have been identified, namely family and employment domains, and (3) to discuss the factors involved in the language choice used in this community. The research methods utilized in this study are fieldworks, questionnaire, semi-structured interviews, and observations. Data collection was carried out in Pontian and Pasir Gudang, Johor as well as in Pandamaran, Selangor. A total of 200 informants who were randomly selected from the Bugis community participated in this study. Data analysis was carried out based on the Fishman’s (1972) domain analysis. The results of the study reveal that most of the bilingual Bugis community prioritize Malay as the main language in their daily communication. This study provides information on the language choice of the bilingual Bugis community in Peninsular Malaysia, which has adapted to the local language. This study might be beneficial to nation building through the mastery and use of Malay language among minority communities in Malaysia.
Keywords: bilingualism; language choice; Bugis community; Peninsular Malaysia; Domain